2016
DOI: 10.1016/j.pep.2016.02.014
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of an Sf-rhabdovirus-negative Spodoptera frugiperda cell line as an alternative host for recombinant protein production in the baculovirus-insect cell system

Abstract: Cell lines derived from the fall armyworm, Spodoptera frugiperda (Sf), are widely used as hosts for recombinant protein production in the baculovirus-insect cell system (BICS). However, it was recently discovered that these cell lines are contaminated with a virus, now known as Sf-rhabdovirus [1]. The detection of this adventitious agent raised a potential safety issue that could adversely impact the BICS as a commercial recombinant protein production platform. Thus, we examined the properties of Sf-RVN, an Sf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 23 publications
2
53
3
Order By: Relevance
“…Our basic approach was to use cell-free media filtrates from our Sf9 and Sf21 cultures, which were known to be contaminated with the Sf-rhabdoviral variants described above, to inoculate Sf-RVN, a novel Sf line that has no Sf-rhabdovirus (Maghodia et al, 2016). One day after inoculation, the Sf-RVN cells were extensively washed, returned to the incubator, and then samples were harvested and used to prepare cell lysates at various times post-inoculation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our basic approach was to use cell-free media filtrates from our Sf9 and Sf21 cultures, which were known to be contaminated with the Sf-rhabdoviral variants described above, to inoculate Sf-RVN, a novel Sf line that has no Sf-rhabdovirus (Maghodia et al, 2016). One day after inoculation, the Sf-RVN cells were extensively washed, returned to the incubator, and then samples were harvested and used to prepare cell lysates at various times post-inoculation.…”
Section: Resultsmentioning
confidence: 99%
“…Our sequence analyses revealed multiple single nucleotide polymorphisms that can be used to distinguish the Sf-rhabdovirus variants harbored by different Sf cell lines. Interestingly, PCR analysis of genomic DNAs isolated from our Sf9, Sf21, and Sf-rhabdovirus-negative (Sf-RVN; (Maghodia et al, 2016) cells revealed none of the integrated Sf-rhabdoviral sequences detected by Hashimoto and coworkers (2017) in the Sf9 L5814 cell genome. Subsequently, we found the Sf-rhabdoviral variants produced by our Sf9 and Sf21 cells were both able to establish persistent, productive infections in Sf-RVN cells, which is the first direct evidence Sf-rhabdoviruses are infectious for Sf cells.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…marginale (Pierlé et al 2013), R. pomeroyi (Green et al 2013), L. acidophilus (Askelson et al 2014), C. reinhardtir (Erpel et al 2016), Y. lipolytica (Matthaus et al 2014), S. elongates (van der Woude et al 2016) & baculovirus (Maghodia et al 2016). While it is encouraging that codon optimization software programs are used for a variety of species and purposes, most of the papers…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%